Internet-Mobile-Based Acceptance and Commitment Therapy (ACT) Against Diabetes Mellitus Distress: A Systematic Review - Susila, Wahyu Dini Candra; Nurwahidah, Nurwahidah; Metrikayanto, Wahyu Dini (Adi Husada Nursing Journal, 2023)
An intervention that can be used by nurses who treat DM patients is acceptance and commitment therapy (ACT). ACT is a therapy that has the goal of helping individuals to be able to accept unpleasant self-experiences and be willing to commit to behaving and acting in accordance with values so as to achieve a more valuable life. Diabetes can also cause stress which is usually called diabetes distress. One strategy that can be used at this time is the use of the internet–mobile–based interventions. Systematic review is based on Preferred Reporting Items for Systematic Review and Meta-Analyzed (PRISMA). The databases used are Scopus, Proquest, Science Direct, and Pubmed which are limited to publications for the last 5 years from 2018 to 2022, full-text articles, and use English. The keywords used in the search for articles are "Diabetes Mellitus" AND "Acceptance and Commitment Therapy" AND "mobile" AND "Distress". This systematic review uses 10 articles that meet the inclusion criteria. The initial literature search yielded 56 articles. There are 10 articles selected for review. conclusions: The results of this systematic review provide evidence for policymakers to consider alternative interventions using this method to reduce distress in patients with diabetes mellitus.